Exercise and pregnancy in recreational and elite athletes: 2016 evidence summary from the IOC expert group meeting, Lausanne. Part 2—the effect of exercise on the fetus, labour and birth. Issue 21 (12th October 2016) - Bø, Kari; Artal, Raul; Barakat, Ruben; Brown, Wendy; Dooley, Michael; Evenson, Kelly R; Haakstad, Lene A H; Larsen, Karin; Kayser, Bengt; Kinnunen, Tarja I; Mottola, Michelle F; Nygaard, Ingrid; et al.
Abstract : This is Part 2 of 5 in the series of evidence statements from the IOC expert committee on exercise and pregnancy in recreational and elite athletes. Part 1 focused on the effects of training during pregnancy and on the management of common pregnancy-related symptoms experienced by athletes. In Part 2, we focus on maternal and fetal perinatal outcomes.